Terrible typhoid Mary : a true story of the deadliest cook in America - Bartoletti, Susan Campbell (Houghton Mifflin Harcourt, 2015)
"What happens when a person's reputation has been forever damaged? With archival photographs and text among other primary sources, this riveting biography of Mary Mallon by the Sibert medalist and Newbery Honor winner Susan Bartoletti looks beyond the tabloid scandal of Mary's controversial life. How she was treated by medical and legal officials reveals a lesser-known story of human and constitutional rights, entangled with the science of pathology and enduring questions about who Mary Mallon really was. How did her name become synonymous with deadly disease? And who is really responsible for the lasting legacy of Typhoid Mary? This thorough exploration includes an author's note, timeline, annotated source notes, and bibliography" --